2001
DOI: 10.1007/s11926-996-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors in the Spondyloarthropathies: New insights into the role of HLA-B27

Abstract: Spondyloarthropathies represent complex genetic diseases whose development is influenced by environmental factors. Estimates suggest that three to nine loci may be responsible for the majority of the genetic susceptibility to ankylosing spondylitis. The only susceptibility locus identified to date in multiple populations is HLA-B, where several HLA-B27 alleles (subtypes) are strongly associated with disease. Recent evidence implicates cytochrome P450 2D6 as a second locus, although its influence on overall ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Colbert et al showed that in ReA during the antigen processing and assembly pathway in the endoplasmic reticulum, HLA-B27 has a tendency to misfold even without any ␤ 2 -microglobulin or peptide deficiency. This misfolding implicates the B pocket of the molecule and can lead to a stress response, which could increase the production of proinflammatory cytokines by activation of the NF-B (35,36) Additional mechanisms have been proposed to explain the role of HLA-B27. In some genetically predisposed subjects, HLA-B27 appears to lack the ability to eliminate infected macrophages normally (92,111), improving the intracellular survival of pathogens (183).…”
Section: Hostmentioning
confidence: 99%
“…Colbert et al showed that in ReA during the antigen processing and assembly pathway in the endoplasmic reticulum, HLA-B27 has a tendency to misfold even without any ␤ 2 -microglobulin or peptide deficiency. This misfolding implicates the B pocket of the molecule and can lead to a stress response, which could increase the production of proinflammatory cytokines by activation of the NF-B (35,36) Additional mechanisms have been proposed to explain the role of HLA-B27. In some genetically predisposed subjects, HLA-B27 appears to lack the ability to eliminate infected macrophages normally (92,111), improving the intracellular survival of pathogens (183).…”
Section: Hostmentioning
confidence: 99%